Stock assessment of the round herring, Etrumeus teres (De Kay, 1842) in the Egyptian sector of Red Sea - Mehanna, Sahar Fahmy; El-Gammal, Fahmy I (Indian Journal of Fisheries, 2011)
Age and growth, mortality, length cohort analysis and stock size of Etrumeus teres collected from the Egyptian sector of Red Sea during the period from October 2001 to May 2003 have been estimated from the length-frequency distribution data of more than 3000 fishes. Age composition was determined using otolith’s reading as well as the Bhattacharya’s method and the results showed that E.teres ranged from 1 to 3 years old. The von Bertalanffy growth parameters were: K=0.59 year-1, L∞=26.97 cm and t0 = -0.4 year. The instantaneous rates of total, natural and fishing mortality were estimated as 2.33, 0.87 and 1.46 year-1 respectively. Exploitation rate was estimated as 0.63. Stock size of E.teres has been estimated by cohort analysis. The study shows that a further increase in fishing effort will not be economical and would further endanger recruitment.